2022
DOI: 10.3389/fpubh.2022.807526
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Literacy of Middle School Students and Its Influencing Factors: A Cross-Sectional Study in Chongqing, China

Abstract: Nutrition literacy plays an important role in children's dietary habits and nutrition. This study aimed to analyse the status of nutrition literacy and its influencing factors amongst middle school students in Chongqing, China. “Nutrition literacy scale for middle school students in Chongqing” was used in 29 districts of Chongqing in September 2020. The scores of nutrition literacy and its' three sub-domains (functional, interactive and critical nutrition literacy) were divided into low and high groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
2
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 57 publications
(63 reference statements)
8
14
2
13
Order By: Relevance
“…In Lebanon, only one preliminary study was conducted to assess the NL of adolescents and observed a lower percentage of poor NL (21.2%) than that currently reported (28). Moreover, our findings with regards to adolescents' NL is similar to that reported among Chinese (27), and Turkish adolescents (29,30). Our findings are warrantable and could be partially explained by the fact that almost all (91.0%) of the adolescents reported not receiving nutrition education in their schools' curriculum in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…In Lebanon, only one preliminary study was conducted to assess the NL of adolescents and observed a lower percentage of poor NL (21.2%) than that currently reported (28). Moreover, our findings with regards to adolescents' NL is similar to that reported among Chinese (27), and Turkish adolescents (29,30). Our findings are warrantable and could be partially explained by the fact that almost all (91.0%) of the adolescents reported not receiving nutrition education in their schools' curriculum in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, food literacy and nutrition literacy were shown to be of better status in multiple countries outside the MENA region, even among adolescent participants. This was evident in recent studies conducted in China [ 74 ], Turkey [ 62 , 63 , 64 ], the U.S. [ 75 ], and Ghana [ 76 ], with all emphasizing adequate nutrition literacy in the sampled population, showing good competencies in most or even all food-literacy and nutrition-literacy components. Besides, good nutrition-literacy levels and basic food literacy were recorded in Greece [ 67 ] and Canada [ 77 ], respectively.…”
Section: Resultsmentioning
confidence: 75%
“…To the best of our knowledge, few studies have examined the association between NL of adolescents and BMI or overweight/obesity. Our previous studies found that BMI is a determinant of NL among middle school students in Chongqing, China ( 24 ). Using multinomial logistic regression model and subgroup analyses, our findings suggested inverse relationships between NL, FNL, and overweight/obesity, different from some previous studies ( 11 , 18 ).…”
Section: Discussionmentioning
confidence: 99%